Laparoscopic assisted transsanal endorectal pull-through procedure for Hirschsprung’s disease in children: Our experience - Hoque, Md Mozammel; Hannan, Md Jafrul (Journal of Paediatric Surgeons of Bangladesh, 2018)
Background: Trans anal endorectal pullthrough procedure is primarily performed for rectosigmoid aganglionosis, generally with excellent results. There is evidence that overstreching the anus and tension traction in the sigmoid colon during the procedure could impair the continence of the patient. Trans anal pull-through for Hirschsprung’s disease with laparoscopic assistance is gaining popularity. We describe our early clinical results after laparoscopic assisted endorectal colon pull-through for Hirschsprung’s disease. Materials and methods: From july 2013 to june 2016 ,a total of 28 patients were treated with Hirschsprung’s disease randomized for laparocopic assisted trans anal pull-through. Of which male were 18 and female 10 . Age ranged from 19 days to 3.5 years. The technique was 3 small (5mm) abdominal ports. A colon pedicle preserving the marginal artery is fashioned laparoscopically. The rectal mobilization is performed transanally using an endorectal sleeve technique. The anastomosis is performed transanally 1cm above the dentate line. Results: The median operative time was 125 min (range 110- 180min). Follow up period 15 days to 12months. Overall functional outcome was good in all cases. Three cases developed mild enterocolitis. One patient developed fecal incontinence and soiling. Conclusion: Laparoscopic assisted colon pull-through for Hirschsprung’s disease is simple and easy to perform with minimal dissection which cause less damage to the internal sphincter and pelvic nerves. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (1): 20-23